Current Surgical Treatment Options of Rheumatoid Shoulder - Aydin, Nuri; Aslan, Lercan; Lehtinen, Janne; Hamuryudan, Vedat (Current Rheumatology Reviews, 2018)
Background: Rheumatoid Arthritis (RA) is an inflammatory disease with destructive pattern. Patients are suffering from pain and decreased functional outcome as the disease progress. Certain joints are widely discussed in the literature as well as shoulder girdle, but shoulder girdle surgical treatment options' indications and superiorities to each other were not compared entirely. Materials and Methods: Treatment options, such as; synovectomy and bursectomy, resection interposition arthroplasty, hemiarthroplasty, humeral resurfacing arthroplasty, anatomical total shoulder arthroplasty and reverse shoulder arthroplasty, are examined for their timing, advantages, disadvantages and comparison. Results: Patients' age is the main factor about the decision making in rheumatoid arthritis. Young aged patients demand high activity level, but as a result loosening of the implant is frequently encountered. Thus, the protection of the bone stock as much as possible must be the priority. For a young patient with disabling pain should be evaluated for less invasive surgeries such as; synovectomy and bursectomy, resection interposition arthroplasty and also for hemiarthroplasty for preservation of glenoid bone stock. But rotator cuff status, glenoid bone stock evaluation and grading of the glenoid defect become more important in old aged patients and the correct decision making can only be made by combining these factors. Conclusions: Age, functional demand, rotator cuff status and adequacy of glenoid bone stock are defined as major criteria for an optimal treatment. Even though RA patients require additional care for a good functional outcome; with correct decision-making, high quality of life is achievable.
Keywords: inflammatory disease